The Influence of E-Service Quality, E-Trust, and Product Quality on Purchasing Decisions Through the Allofresh Transmart Application (Sainteknol : Jurnal Sains dan Teknologi, 2022)
This study aims to analyze the effect of E-Service Quality, E-Trust, and Product Quality on Purchasing Decisions Through the Allofresh Transmart Application in the City of Semarang. This study used a quantitative approach using observational data from 100 Allofresh users who were analyzed using a multiple regression approach through SPSS25 software. This study found that E-Service Quality, E-Trust, and Product Quality have a positive and significant impact on purchasing decisions for the Allofresh Transmart application. Simultaneously, all variables in the study also have a significant influence on purchasing decisions, and are able to explain 61.6% percent of the variations in the influence of purchasing decisions. This research proves the need for more effort from companies to pay attention to aspects of E-Service Quality, E-Trust, and Product Quality in influencing consumer purchasing decisions to increase the number of product sales.